2022
DOI: 10.3390/cells11050824
|View full text |Cite
|
Sign up to set email alerts
|

Mechanomimetic 3D Scaffolds as a Humanized In Vitro Model for Ovarian Cancer

Abstract: The mechanical homeostasis of tissues can be altered in response to trauma or disease, such as cancer, resulting in altered mechanotransduction pathways that have been shown to impact tumor development, progression, and the efficacy of therapeutic approaches. Specifically, ovarian cancer progression is parallel to an increase in tissue stiffness and fibrosis. With in vivo models proving difficult to study, tying tissue mechanics to altered cellular and molecular properties necessitate advanced, tunable, in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…SKOV-3 ovary cancer cell line can be cultured with the decellularized scaffold with very low toxicity than reported previously by Paradiso et al [17]. This study showed cytotoxicity at a level of up to 7.4% while Paradiso et al study indicated up to 14% of cell death with the synthetic scaffold.…”
Section: Discussionmentioning
confidence: 43%
“…SKOV-3 ovary cancer cell line can be cultured with the decellularized scaffold with very low toxicity than reported previously by Paradiso et al [17]. This study showed cytotoxicity at a level of up to 7.4% while Paradiso et al study indicated up to 14% of cell death with the synthetic scaffold.…”
Section: Discussionmentioning
confidence: 43%
“…Abundance studies demonstrated that mechanical stimulation plays an essential role in wide biological processes [ 107 111 ]. A variety of mechanical stimulation, fluid shear stress, tension, and (hydrostatic) compression, and matrix stiffness can modulate differentiation of stem cell [ 112 ], immune response [ 113 ], cellular apoptosis [ 114 ], tumor development [ 115 ] and bone remodeling [ 116 ]. An intimate connection between bioelectricity and mechanical forces has been acknowledged, wherein intracellular bioelectric signals and mechanical signals can reciprocally transfer.…”
Section: Endogenous Electrical Signalsmentioning
confidence: 99%
“…Both the ECM itself and the mechanical stimuli is triggered by ECM stiffening and can activate cell membrane receptors and several mechanosensors, thereby modulating the malignant phenotype of tumor and stromal cells. 13,16 By directly stimulating cell survival, migration, proliferation and differentiation, the abnormal ECM influences the development of cancer. 15,17 By deregulating stromal cell behavior and modulating signaling cascades mediated by interactions with cell surface receptors, the remodeled ECM and its degradation fragments may promote the emergence of an oncogenic microenvironment.…”
Section: Matrix Composition Structure and Function In Osccmentioning
confidence: 99%
“…To understand the specific features of the ECM in solid tumors is necessary to develop approaches to influence its negative effects. Both the ECM itself and the mechanical stimuli is triggered by ECM stiffening and can activate cell membrane receptors and several mechanosensors, thereby modulating the malignant phenotype of tumor and stromal cells 13,16 . By directly stimulating cell survival, migration, proliferation and differentiation, the abnormal ECM influences the development of cancer 15,17 .…”
Section: Matrix Composition Structure and Function In Osccmentioning
confidence: 99%